2013
DOI: 10.1159/000357028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prochlorperazine on Normal Vestibular Ocular and Perceptual Responses: A Randomised, Double-Blind, Crossover, Placebo-Controlled Study

Abstract: Background: The present study investigated whether prochlorperazine affects vestibulo-ocular reflex (VOR) and vestibulo-perceptual function. Methods: We studied 12 healthy naïve subjects 3 h after a single dose of oral prochlorperazine 5 mg in a randomised, placebo-controlled, double-blind, crossover study in healthy young subjects. Two rotational tests in yaw were used: (1) a threshold task investigating perceptual motion detection and nystagmic thresholds (acceleration steps of 0.5°/s2) and (2) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Furthermore, the limitations of the trial in this research are recognized, which included a modest dose of betahistine (24 mg), a small sample size, and the use of healthy participants. This research is comparable to those of Patel et al (2014) [ 18 ] and Gordon et al (2003) [ 19 ] in terms of the overall outcome of the study, whereby no effect of medication was found on the vestibulo-ocular reflex. Patel et al examined the impact of prochlorperazine on normal vestibular ocular and perceptual responses in a placebo-controlled, randomized, double-blind crossover research.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the limitations of the trial in this research are recognized, which included a modest dose of betahistine (24 mg), a small sample size, and the use of healthy participants. This research is comparable to those of Patel et al (2014) [ 18 ] and Gordon et al (2003) [ 19 ] in terms of the overall outcome of the study, whereby no effect of medication was found on the vestibulo-ocular reflex. Patel et al examined the impact of prochlorperazine on normal vestibular ocular and perceptual responses in a placebo-controlled, randomized, double-blind crossover research.…”
Section: Discussionsupporting
confidence: 89%
“…Patel et al examined the impact of prochlorperazine on normal vestibular ocular and perceptual responses in a placebo-controlled, randomized, double-blind crossover research. In comparison to placebo, prochlorperazine had no effect on any measure of nystagmus or perceptual vestibular function [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this corresponds to the roughly 0.6°/s VOR variability we measured when chair velocity was below 1°/s. Another approach has been to measure nystagmic thresholds (Seemungal et al, 2004, Patel et al, 2014), the acceleration at which the first nystagmic fast phase occurred in response to slow yaw velocity ramps. These studies determined a threshold in humans of 0.5°/s/s.…”
Section: Discussionmentioning
confidence: 99%
“…Acute clinical examination revealed unidirectional horizontal nystagmus with a torsional component, a positive horizontal head impulse test, unilateral caloric canal paresis, lateropulsion, and no hearing impairment or symptoms/signs of CNS disorder . Of the 24 patients who were administered prochloperazine, only three received these on the day of testing, but the drug has been shown to have no effect upon vestibulo‐reflex or vestibulo‐perceptual function . MRI brain scans were not routinely performed, but when done on hospital arrival ( n = 3), no abnormalities were detected.…”
Section: Methodsmentioning
confidence: 99%